Prisma (1967): Creative context and analysis of the work of the Peruvian composer Enrique Pinilla - Magán Palomino, Michael Augusto (2024)
Enrique Pinilla was a Peruvian composer who belonged to the Generation of 50. The decade of 1950 “represented the end of an era and the starting point of another”, because the compositional activity in Latin America underwent changes that led to a great variety of styles and diversity of aesthetics. In this sense, it is pointed out that Pinilla's work is small and attributes this to the creative diversification in his works. Pinilla obtained the Fulbright scholarship to study electronic music at Columbia University under the guidance of the American composer Vladimir Ussachevsky and there he composed his only electronic work, Prisma, for magnetic tape, as stated in the catalogue prepared by Edgar Valcárcel in 1987.